Diagnosis of PTEN mosaicism: the relevance of additional tumor DNA sequencing. A case report and review of the literature - Mathias Cavaillé; Delphine Crampon; Viorel Achim; Virginie Bubien; Nancy Uhrhammer; Maud Privat; Flora Ponelle-Chachuat; Mathilde Gay-Bellile; Mathis Lepage; Zangbéwendé Guy Ouedraogo; Natalie Jones; Yannick Bidet; et al. (BMC, 2023)
Abstract Background PTEN hamartoma syndrome (PHTS) is an autosomal dominant disorder characterized by pathogenic variants in the tumor suppressor gene phosphatase and tensin homolog (PTEN). It is associated with an increased risk of muco-cutaneous features, hamartomatous tumors, and cancers. Mosaicism has been found in a few cases of patients with de novo PHTS, identified from blood samples. We report a PHTS patient with no variant identified from blood sample. Constitutional PTEN mosaicism was detected through sequencing of DNA from different tumoral and non-tumoral samples. Case presentation Our patient presented clinical Cowden syndrome at 56 years of age, with three major criteria (macrocephaly, Lhermitte Duclos disease, oral papillomatosis), and two minor criteria (structural thyroid lesions, esophageal glycogenic acanthosis). Deep sequencing of PTEN of blood leukocytes did not reveal any pathogenic variants. Exploration of tumoral (colonic ganglioneuroma, esophageal papilloma, diapneusia fibroids) and non-tumoral stomach tissues found the same PTEN pathogenic variant (NM_000314.4 c.389G > A; p.(Arg130Gln)), with an allelic frequency of 12 to 59%, confirming genomic mosaicism for Cowden syndrome. Conclusions This case report, and review of the literature, suggests that systematic tumor analysis is essential for patients presenting PTEN hamartoma syndrome in the absence of any causal variant identified in blood leukocytes, despite deep sequencing. In 65 to 70% of cases of clinical Cowden syndrome, no pathogenic variant in the PTEN is observed in blood samples: mosaicism may explain a significant number of these patients. Tumor analysis would improve our knowledge of the frequency of de novo variations in this syndrome. Finally, patients with mosaicism for PTEN may not have a mild phenotype; medical care identical to that of heterozygous carriers should be offered.